Does Cognitive Style Moderate Expected Evaluation and Adolescents' Creative Performance: An Empirical Study. (2nd April 2020) - Lei, Weina; Deng, Wenbo; Zhu, Rongjuan; Runco, Mark A.; Dai, David Yun; Hu, Weiping
ABSTRACT: Two studies investigated the effects of cognitive and school environmental factors on adolescents' creative performance. The first study tested the effects of expected evaluation and cognitive style on creativity among 89 high school students. The second study tested the effects of evaluation type and cognitive style on creativity among 92 high school students. Study 1 found main effects of expected evaluation and cognitive style on creativity. The interaction between expected evaluation and cognitive style was statistically significant. Under an experimental condition of expected evaluation, field‐dependent adolescents performed more creatively (i.e., higher originality) than those without expected evaluation. Study 2 uncovered main effects of expected evaluation type and cognitive style on creativity but no interactions between expected evaluation type and cognitive style. Adolescents performed better on the dimension of flexibility in a controlling evaluation condition, compared with adolescents in informational evaluation condition, and field‐independent adolescents showed more fluency and originality than field‐dependent adolescents. Together, this research provides a better understanding of the effects of expected evaluation and cognitive style on adolescents' creative performance. Implications for further research are discussed.